1992
DOI: 10.1007/bf01987898
|View full text |Cite
|
Sign up to set email alerts
|

The clearance rate of plasma kallikrein by the liver increases during the acute-phase response to inflammation

Abstract: The effect of the acute-phase response on the clearance rate of plasma kallikrein by the exsanguinated liver was studied in three groups of rats: a control group and two other groups that received either turpentine or an endogenous pyrogen preparation. The plasma kallikrein clearance rates were significantly higher in both inflamed groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
5
2
1
Order By: Relevance
“…Since all livers were analyzed by histological examination and produced the same profile with almost complete inactivation of the Kupffer cells, it is possible that the activation of the inflammatory cascade precedes the cell inactivation. With regard to the role of the acute-phase reaction in the hepatic clearance, we have already shown that after an inflammatory stimulus induced by turpentine oil, the hepatic clearance of RPK increased (20) whereas that of tPA decreased (19). Kupffer cells are not directly involved in RPK internalization (22), but we now confirm that the inflammatory stimulus evokes a higher receptor expression that mediates the hepatic internalization of RPK, independently of the initial stimulus.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Since all livers were analyzed by histological examination and produced the same profile with almost complete inactivation of the Kupffer cells, it is possible that the activation of the inflammatory cascade precedes the cell inactivation. With regard to the role of the acute-phase reaction in the hepatic clearance, we have already shown that after an inflammatory stimulus induced by turpentine oil, the hepatic clearance of RPK increased (20) whereas that of tPA decreased (19). Kupffer cells are not directly involved in RPK internalization (22), but we now confirm that the inflammatory stimulus evokes a higher receptor expression that mediates the hepatic internalization of RPK, independently of the initial stimulus.…”
Section: Discussionsupporting
confidence: 69%
“…With regard to the role of the acute‐phase reaction in the hepatic clearance, we have already shown that after an inflammatory stimulus induced by turpentine oil, the hepatic clearance of RPK increased (20) whereas that of tPA decreased (19). Kupffer cells are not directly involved in RPK internalization (22), but we now confirm that the inflammatory stimulus evokes a higher receptor expression that mediates the hepatic internalization of RPK, independently of the initial stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an in- flammatory stimulus the hepatic clearance rate of rat plasma kallikrein increased (11), in contrast to the tPA behavior now described. Different behavior during endocytosis of proteins that share a common plasma membrane receptor has already been described: epidermal growth factor and transforming growth factor-a compete for the same receptor with different affinities, which could be a consequence of differences in the mechanisms of intracellular processing (24).…”
Section: Discussioncontrasting
confidence: 56%
“…During the AP response the clearance rate of plasma-kallikrein by the perfused rat liver increases (11); in contrast, the liver uptake of an asialoglycoprotein decreases during the AP response (12), suggesting that the mechanism of endocytosis mediated by different lectins is distinctly modified during the AP response. We have shown that tPA and plasma kallikrein share a common pathway for liver clearance (13).…”
mentioning
confidence: 99%